International structure and China's energy security - Ventura, Brian C. (International University of Japan, 2008)
The rapid rise of China's energy consumption has attracted attention to its capability and vulnerability as a major post cold war power. Faced with the need to build closer ties to energy producing regimes to fuel its economic growth and maintain domestic stability. China's economic clout and political influence are being tested by the existing unipolar and anarchic international structure. This study examines how China's energy security is shaped by the international structure and how, in return, its actions as a major power affects the international system. This study advances five propositions pointing out the importance of energy security to China's position as a rising power. China's energy general and specific policy objectives were reviewed and its energy activities in Central Asia, Russia, Southeast Asia, Middle East, Africa and Americas were also examined.